DETERMINE THE THERMAL EFFECTS OF VACUUM SECLUDE PANEL USING A NON-FIXED LEVELED SOURCE SENSOR - Atkins, Prof. Haddock; Roy , Prof. Anirban Roy; Wu , Prof. Zhiang Wu (International Journal of Multidisciplinary Research and Studies, 2021)
Reducing the energy consumption of buildings is necessary to achieve the goals and regulations of the European Union. One way to reduce energy consumption is to use vacuum insulated panels (VIPs) on the building envelope. Field measurements are required to ensure that the declared thermal properties of the VIP match the installed panels. Using the Transient Plane Source (TPS) method, you can quickly measure the thermal properties of a variety of materials. However, due to the large isotropic nature of the VIP, it is difficult to interpret the temperature rise of the TPS sensor. In this article, we will compare polystyrene and polystyrene and aluminum foil analysis solutions, numerical simulations, and TPS measurements. Instead of VIP, polystyrene and aluminum were used to increase the number of installations. Numerical simulation samples were validated by comparing the simulated temperature rise with a polystyrene sample analysis solution. The simulated temperature rise in the polystyrene sample after 40 seconds was 7.8% higher than the TPS calculation. Loss of TPS sensor wire, inaccuracy in material parameters, and surface resistance can account for the deviation.12